Iron-based Prussian blue positive electrode material and preparation method and application thereof
By preparing an iron-based Prussian blue cathode material with a hollow porous spherical structure formed by the stacking of cubic nanoparticles, the problem of insufficient rate performance and cycle performance of iron-based Prussian blue materials in sodium-ion batteries was solved, and the electrochemical performance and structural stability of the material were improved.
Patent Information
- Application Number
- CN202511407612.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-28
- Publication Date
- 2026-01-13
AI Technical Summary
Iron-based Prussian blue materials prepared by existing methods exhibit poor rate performance and cycle performance when used as cathode materials for sodium-ion batteries.
Iron-based Prussian blue cathode material with a hollow porous spherical structure formed by the stacking of cubic nanoparticles is used. By controlling the average particle size and wall thickness of the hollow porous spherical structure, the specific surface area is increased, the diffusion path of sodium ions and electrons is shortened, and a buffer space is provided to improve the structural stability.
Excellent rate performance and cycle performance of iron-based Prussian blue cathode material in sodium-ion batteries were achieved, the electrolyte contact area and structural stability were enhanced, and the sodium ion diffusion path was shortened.
Smart Images

Figure CN121317812A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cathode material technology, and in particular to iron-based Prussian blue cathode materials, their preparation methods, and applications. Background Technology
[0002] Prussian blue-based materials (PBAs) have become a popular choice for cathode materials in sodium-ion batteries due to their advantages such as low cost, fast ion transport, structural stability, and environmental friendliness. Iron-based Prussian blue-based materials (Fe-PBAs), in particular, have a very broad prospect for industrial application due to the abundance of iron resources. However, iron-based Prussian blue-based materials prepared by existing methods still suffer from poor rate performance and cycle performance when used as cathode materials in sodium-ion batteries. Summary of the Invention
[0003] Therefore, it is necessary to provide an iron-based Prussian blue cathode material, its preparation method, and its application to address the above problems. When used as a cathode material for sodium-ion batteries, this iron-based Prussian blue cathode material exhibits both excellent rate performance and cycle performance.
[0004] A type of iron-based Prussian blue cathode material, wherein the molecular formula of the iron-based Prussian blue cathode material is: Wherein, 0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 1, and the iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles, the average particle size of the hollow porous spherical structure is 0.3 μm-8 μm, and the wall thickness of the hollow porous spherical structure is 0.08 μm-2 μm.
[0005] In one embodiment, the specific surface area of the hollow porous spherical structure is 70 m². 2 / g-150m 2 / g.
[0006] A method for preparing the iron-based Prussian blue cathode material includes the following steps:
[0007] Ferric molybdate microsphere powder and solvent were formulated into a suspension;
[0008] by Based on the condition that 0 < x ≤ 2, 0 < y ≤ 1, and 0 < z ≤ 1, Na4Fe(CN)6·10H2O powder or Na4Fe(CN)6·10H2O aqueous solution is placed in the suspension, and then stirred at room temperature and subjected to an ion exchange reaction. After separation and drying, iron-based Prussian blue cathode material is obtained. When Na4Fe(CN)6·10H2O powder is placed in the suspension, the solvent in the suspension includes at least water.
[0009] In one embodiment, the step of preparing a suspension from the ferric molybdate microsphere powder and the solvent further satisfies at least one of the following conditions:
[0010] (1) The average particle size of the iron molybdate microspheres is 0.28 μm-6 μm;
[0011] (2) The preparation method of the iron molybdate microsphere powder includes the following steps: preparing an iron source, a molybdenum source and a solvent into a mixed solution, then subjecting the mixed solution to a solvothermal reaction, and obtaining iron molybdate microsphere powder by separation and drying;
[0012] (3) The solvent is selected from water and / or organic solvents.
[0013] In one embodiment, the method for preparing the ferric molybdate microsphere powder further satisfies at least one of the following conditions:
[0014] (1) The mass ratio of the iron source to the molybdenum source is 0.8:1-2.5:1;
[0015] (2) The iron source is selected from at least one of ferric nitrate, ferric chloride, and ferric sulfate;
[0016] (3) The molybdenum source is selected from ammonium heptamolybdate and / or sodium molybdate;
[0017] (4) The temperature of the solvothermal reaction is 120℃-200℃, and the reaction time is 10h-24h;
[0018] (6) The drying temperature is 60℃-100℃ and the drying time is 8h-24h.
[0019] In one embodiment, in the step of placing Na4Fe(CN)6·10H2O powder or Na4Fe(CN)6·10H2O aqueous solution in the suspension, the mass ratio of the iron molybdate microsphere powder to Na4Fe(CN)6·10H2O is 1:3.5-1:4.5.
[0020] In one embodiment, when an aqueous solution of Na4Fe(CN)6·10H2O is placed in the suspension, the solvent in the suspension includes at least an organic solvent and also satisfies at least one of the following conditions:
[0021] (1) The suspension contains a surfactant, wherein the mass ratio of the iron molybdate microsphere powder to the surfactant is 1:10-1:30;
[0022] (2) The Na4Fe(CN)6·10H2O solution contains a complexing agent, wherein the mass ratio of Na4Fe(CN)6·10H2O to the complexing agent is 1.2:1-1.8:1.
[0023] In one embodiment, the method for preparing the iron-based Prussian blue cathode material further satisfies at least one of the following conditions:
[0024] (1) In the step of stirring and carrying out the ion exchange reaction at room temperature, the ion exchange reaction time is 1.5h-8h;
[0025] (2) In the drying step, the drying temperature is 60℃-120℃ and the drying time is 8h-24h.
[0026] A positive electrode sheet prepared using the aforementioned iron-based Prussian blue positive electrode material.
[0027] A sodium-ion battery prepared using the aforementioned positive electrode sheet.
[0028] The iron-based Prussian blue cathode material of the present invention has a hollow porous spherical structure formed by the stacking of cubic nanoparticles. By controlling the average particle size and wall thickness of the hollow porous spherical structure, the iron-based Prussian blue cathode material has a large specific surface area, which can effectively increase the contact area between the electrolyte and the cathode material, increase the number of reactive sites, and shorten the diffusion path of sodium ions and electrons, thereby improving the rate performance of the cathode material. On the other hand, it can provide sufficient buffer space for sodium ion transport, effectively alleviate the volume change of the cathode material during charge and discharge cycles, enhance structural stability, and improve the cycle performance of the cathode material. Thus, the iron-based Prussian blue cathode material of the present invention has both excellent rate performance and cycle performance when used as a cathode material for sodium-ion batteries. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 This is a scanning electron microscope image of the iron-based Prussian blue cathode material of Example 1 of the present invention;
[0031] Figure 2 This is a transmission electron microscope (TEM) image of the iron-based Prussian blue cathode material of Example 1 of the present invention;
[0032] Figure 3 The X-ray diffraction pattern of the iron-based Prussian blue cathode material of Example 1 of the present invention is shown below.
[0033] Figure 4 This is a graph showing the specific surface area of the iron-based Prussian blue cathode material in Example 1 of the present invention.
[0034] Figure 5 This is a scanning electron microscope image of the iron molybdate nanospheres in Example 1 of the present invention;
[0035] Figure 6 This is the X-ray diffraction pattern of the iron molybdate nanospheres in Example 1 of the present invention;
[0036] Figure 7 This is a scanning electron microscope image of the iron-based Prussian blue cathode material of Example 2 of the present invention;
[0037] Figure 8 This is a scanning electron microscope image of the iron-based Prussian blue cathode material of Example 3 of the present invention;
[0038] Figure 9 This is a scanning electron microscope image of the iron-based Prussian blue cathode material of Example 4 of the present invention;
[0039] Figure 10 This is a scanning electron microscope image of the iron-based Prussian blue cathode material of Comparative Example 1 of the present invention;
[0040] Figure 11 This is a graph showing the specific surface area of the iron-based Prussian blue cathode material in Comparative Example 1 of this invention.
[0041] Figure 12 This is a comparison chart of the rate performance of the iron-based Prussian blue cathode materials in Example 1 and Comparative Example 1 of the present invention;
[0042] Figure 13 This is a cycle performance diagram of the iron-based Prussian blue cathode material of Example 1 of the present invention;
[0043] Figure 14 This is a cycle performance diagram of the iron-based Prussian blue cathode material of Comparative Example 1 of the present invention. Detailed Implementation
[0044] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments or examples only and is not intended to be limiting of the invention.
[0046] The iron-based Prussian blue cathode material provided by this invention has the following molecular formula: Wherein, 0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 1, and the iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles, the average particle size of the hollow porous spherical structure is 0.3 μm-8 μm, and the wall thickness of the hollow porous spherical structure is 0.08 μm-2 μm.
[0047] It is understood that in this invention, the primary particles of the iron-based Prussian blue cathode material are cubic nanoparticles, while the secondary particles are hollow porous spherical structures formed by the stacking of cubic nanoparticles. This hollow porous spherical structure has, on the one hand, a large specific surface area, which can effectively increase the contact area between the electrolyte and the cathode material, increase the reactive sites, and shorten the diffusion path of sodium ions and electrons. This is beneficial for achieving rapid diffusion and transport of sodium ions and electrons during the charge and discharge process of sodium-ion batteries, thereby improving the rate performance of the cathode material. On the other hand, it can provide a buffer space for sodium ion transport, effectively alleviate the volume change of the cathode material during charge and discharge cycles, enhance structural stability, and improve the cycle performance of the cathode material.
[0048] Meanwhile, by controlling the average particle size and wall thickness of the hollow porous sphere structure, under this synergistic effect, it is possible to further increase the specific surface area of the hollow porous sphere structure, increase the reactive sites, provide sufficient buffer space for sodium ion transport, and ensure that the hollow porous sphere structure has high structural stability, thereby further improving the rate performance and cycle performance of the cathode material.
[0049] Therefore, the iron-based Prussian blue cathode material of the present invention has a hollow porous spherical structure formed by the stacking of cubic nanoparticles, and by controlling the average particle size and wall thickness of the hollow porous spherical structure, under this synergistic effect, it can be used as a cathode material for sodium-ion batteries to have both excellent rate performance and cycle performance.
[0050] It should be noted that in this invention, the hollow porous spherical structure is a spherical particle with many small pores on the shell surface and a hollow cavity inside. The small pores are formed by the gaps between cubic nanoparticles. Compared with the traditional hollow spherical structure, the hollow porous spherical structure can further form a multi-level pore structure. This multi-level pore structure can not only further shorten the diffusion path of nano-ions and electrons to the nanoscale while ensuring that the hollow porous spherical structure has a strong shell, thus improving the rate performance of the cathode material, but also form a multi-level stress dispersion, which can more effectively resist the volume expansion caused by sodium ion insertion / extraction. In addition, it can also make the cathode material exhibit a lower degree of agglomeration, which can further improve the dispersibility of the cathode material.
[0051] Optionally, the specific surface area of the hollow porous spherical structure is 70 m². 2 / g-150m 2 / g. By controlling the specific surface area of the hollow porous spherical structure, the rate performance and cycle performance of the cathode material can be further improved.
[0052] Meanwhile, the present invention also provides a method for preparing the iron-based Prussian blue cathode material, comprising the following steps:
[0053] S1, ferric molybdate microsphere powder and solvent are formulated into a suspension.
[0054] Specifically, in step S1, the iron molybdate microsphere powder is ultrasonically dispersed in a solvent to prepare a suspension.
[0055] In one embodiment, the solvent is selected from water and / or an organic solvent, preferably water, wherein the organic solvent is preferably ethanol.
[0056] Optionally, the average particle size of the iron molybdate microspheres is 0.28 μm-6 μm; with this setting, the particle size of the hollow porous spherical structure of the iron-based Prussian blue cathode material can be better controlled by controlling the average particle size of the iron molybdate microspheres.
[0057] In this invention, the preparation method of ferric molybdate microsphere powder is not particularly limited. In one embodiment, ferric molybdate microsphere powder is prepared by a solvothermal method.
[0058] Specifically, the preparation method of the iron molybdate microsphere powder includes the following steps: preparing an iron source, a molybdenum source and a solvent into a mixed solution, then subjecting the mixed solution to a solvothermal reaction, and obtaining iron molybdate microsphere powder by separation and drying.
[0059] In one embodiment, in the step of preparing a mixed solution from an iron source, a molybdenum source, and a solvent, the solvent is selected from water and / or an organic solvent, wherein the organic solvent is preferably ethylene glycol.
[0060] In one embodiment, the steps for preparing the mixed solution are as follows: an iron source and a first solvent are prepared into an iron solution, a molybdenum source and a second solvent are prepared into a molybdenum solution, and then the molybdenum solution and the iron solution are mixed to obtain a mixed solution. The first solvent and the second solvent are independently selected from water or organic solvents, and the organic solvent is preferably ethylene glycol.
[0061] Considering the influence of the specific types of the first and second solvents on the iron solution, the molybdenum solution, and the uniform dispersion between them, the components in the iron solution and the components in the mixed solution are adjusted according to the selection of the types of the first and second solvents, as follows:
[0062] When both the first solvent and the second solvent are selected from organic solvents, an acid is also added in the step of preparing the iron solution, wherein the acid is preferably nitric acid.
[0063] The steps for preparing the mixed solution are as follows: an iron source, acid, and organic solvent are prepared to form an iron solution; a molybdenum source and organic solvent are prepared to form a molybdenum solution; then, the iron solution and the molybdenum solution are mixed to obtain the mixed solution. This arrangement facilitates obtaining a uniformly dispersed iron solution, thereby improving the dispersion uniformity of the mixed solution.
[0064] In one embodiment, an iron source and an acid are dissolved in an organic solvent and stirred for 20-40 minutes to prepare an iron solution; a molybdenum source is dissolved in an organic solvent and stirred for 20-40 minutes to prepare a molybdenum solution; then the iron solution is added dropwise to the iron solution and stirred for 1-6 hours to obtain the mixed solution.
[0065] When both the first solvent and the second solvent are selected from water, the steps for preparing the mixed solution are as follows: an iron source and water are mixed to form an iron solution, a molybdenum source and water are mixed to form a molybdenum solution, and then the iron solution and the molybdenum solution are mixed to obtain the mixed solution.
[0066] Furthermore, in the step of mixing the iron solution and the molybdenum solution, glycerol is also added, wherein the mass fraction of glycerol in the mixed solution is 50%-70%.
[0067] Optionally, the mass ratio of the iron source to the molybdenum source is 0.8:1 to 2.5:1; this setting is beneficial for better formation of iron molybdate microsphere powder.
[0068] Furthermore, the iron source is selected from at least one of ferric nitrate, ferric chloride, and ferric sulfate; the molybdenum source is selected from ammonium heptamolybdate and / or sodium molybdate.
[0069] Optionally, the temperature of the solvothermal reaction is 120℃-200℃, and the reaction time is 10h-24h; such settings are beneficial for forming iron molybdate microspheres with uniform size and suitable crystallinity.
[0070] Optionally, the drying temperature is 60℃-100℃ and the drying time is 8h-24h.
[0071] In one embodiment, the separation process in the step of preparing ferric molybdate microsphere powder includes centrifugation and washing, wherein washing is performed using deionized water.
[0072] S2, with Based on the condition that 0 < x ≤ 2, 0 < y ≤ 1, and 0 < z ≤ 1, Na4Fe(CN)6·10H2O powder or Na4Fe(CN)6·10H2O aqueous solution is placed in the suspension, and then stirred at room temperature and subjected to an ion exchange reaction. After separation and drying, iron-based Prussian blue cathode material is obtained. When Na4Fe(CN)6·10H2O powder is placed in the suspension, the solvent in the suspension includes at least water.
[0073] In step S2, Na4Fe(CN)6·10H2O powder or Na4Fe(CN)6·10H2O aqueous solution is placed in the suspension. Under stirring conditions, the ferric molybdate microspheres generate soluble ferrous ions (Fe2+). 2+ ) and molybdate ions (MoO4) 2- Na₄Fe(CN)₆·10H₂O produces soluble Na₂ + And [Fe(CN)6] 4- In this process, MoO4 2- Ions and [Fe(CN)6] 4- An exchange occurs, and simultaneously due to MoO4 2- Ions and [Fe(CN)6] 4- Due to the different diffusion rates, utilizing the Kendall effect, iron ions inside the ferric molybdate microspheres are continuously replaced by sodium ions. The replaced iron ions then react with sodium ions. + [Fe(CN)6] 4- Precipitation reaction forms Nanoparticles, tightly adhered to the surface of ferric molybdate microspheres, undergo continuous ion exchange reactions. As the iron ions within the microspheres are constantly replaced, a hollow structure is formed. The nanoparticles will gradually grow into cubic nanoparticles. As the reaction proceeds, the iron molybdate microspheres become hollow porous spherical structures with small pores formed by the gaps between the cubic nanoparticles on their surface. In other words, the resulting material is an iron-based Prussian blue cathode material with a hollow porous spherical structure formed by the stacking of cubic nanoparticles.
[0074] It is understood that in this invention, ferric molybdate microsphere powder is used as a self-sacrificing template and iron source, and then an ion exchange method is used to exchange iron ions in the ferric molybdate microspheres with sodium ions in the reaction system to generate a product with the chemical formula […]. Iron-based Prussian blue cathode material with (0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 1), wherein the iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles.
[0075] In addition, since the ion exchange reaction is carried out at room temperature, the reaction is mild and the operation is simple, which is conducive to the large-scale production of iron-based Prussian blue cathode materials.
[0076] Optionally, the mass ratio of the ferric molybdate microsphere powder to Na4Fe(CN)6·10H2O is 1:3.5-1:4.5. This setting allows for better control of the average particle size and wall thickness of the hollow porous sphere structure by adjusting the mass ratio of the two components.
[0077] It should be noted that in this invention, Na4Fe(CN)6·10H2O can be placed in a suspension in powder form or as an aqueous solution. Specifically, when Na4Fe(CN)6·10H2O is in powder form, i.e., when Na4Fe(CN)6·10H2O powder is placed in a suspension, the solvent in the suspension must include at least water. This arrangement utilizes the water in the suspension to allow the ferric molybdate microspheres to generate soluble ferrous ions (Fe2+). 2+ ) and molybdate ions (MoO4) 2- ) and Na4Fe(CN)6·10H2O to produce soluble Na + And [Fe(CN)6] 4- This allows for ion exchange reactions to occur at room temperature, forming a hollow porous spherical structure.
[0078] When Na4Fe(CN)6·10H2O is placed in a suspension in the form of an aqueous solution, that is, when the Na4Fe(CN)6·10H2O aqueous solution is placed in the suspension, the solvent in the suspension includes at least an organic solvent, wherein the organic solvent is preferably ethanol. This arrangement utilizes the buffering effect of the organic solvent to effectively control the generation of soluble ferrous ions (Fe2+) from the ferric molybdate microspheres during stirring. 2+ ) and molybdate ions (MoO4) 2- ) and Na4Fe(CN)6·10H2O to produce soluble Na + And [Fe(CN)6] 4- The rate of ion exchange can be controlled, which in turn controls the reaction rate of ion exchange, thus facilitating the formation of iron-based Prussian blue cathode materials with hollow porous spherical structures.
[0079] Optionally, the suspension contains a surfactant, wherein the mass ratio of the ferric molybdate microsphere powder to the surfactant is 1:10-1:30; this setting is beneficial to improving the dispersibility and stability of the ferric molybdate microsphere powder in the suspension.
[0080] Furthermore, the surfactant is selected from nonionic surfactants, and the nonionic surfactant is preferably at least one of polyvinylpyrrolidone, methoxy polyethylene glycol, polyvinyl alcohol, and polyethylene glycol.
[0081] Optionally, the Na4Fe(CN)6·10H2O solution contains a complexing agent, wherein the mass ratio of Na4Fe(CN)6·10H2O to the complexing agent is 1.2:1-1.8:1. This configuration is beneficial for controlling the reaction rate and forming a better hollow porous spherical structure.
[0082] Furthermore, the complexing agent is preferably at least one of trisodium citrate, ethylenediaminetetraacetic acid, and sodium tartrate.
[0083] In step S2, the ion exchange reaction is carried out by stirring at room temperature for 1.5h-8h. By controlling the ion exchange reaction time, the morphology and size of the hollow porous sphere structure can be better controlled, and iron-based Prussian blue cathode material with specific average particle size and wall thickness can be obtained.
[0084] Optionally, the drying temperature is 60℃-120℃, and the drying time is 8h-24h. This setting is beneficial for obtaining iron-based Prussian blue cathode materials with uniform particle size and stable quality.
[0085] It should be noted that the drying method is not particularly limited in this invention. Specifically, in one embodiment, vacuum drying is used.
[0086] In one embodiment, the separation step in step S2 includes centrifugation and washing.
[0087] In addition, the present invention also provides a positive electrode sheet prepared using the aforementioned iron-based Prussian blue positive electrode material.
[0088] Furthermore, a sodium-ion battery prepared using the aforementioned positive electrode sheet. This sodium-ion battery exhibits excellent rate performance and cycle performance.
[0089] The following specific embodiments will further illustrate the iron-based Prussian blue cathode material, its preparation method, and its applications. However, those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified, specific conditions in the embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0090] Example 1
[0091] A solution of iron was prepared by mixing 2.1548 g of Fe(NO3)3·9H2O, 4 mL of HNO3, and 36 mL of ethylene glycol and stirring for 30 min; 1.412 g of ammonium heptamolybdate (NH4)6Mo7O was also prepared. 24A molybdenum solution was prepared by mixing 4H2O and 40 mL of ethylene glycol and stirring for 30 min. Then, the iron solution obtained above was added dropwise to the molybdenum solution and stirred for 6 h to prepare a mixed solution. The mixed solution was then transferred to a 90 mL Teflon-lined stainless steel high-pressure reactor and subjected to a solvothermal reaction at 160°C for 14 h to obtain the reaction product. The reaction product was centrifuged, washed three times with deionized water, and then dried in a vacuum drying oven at 60°C for 24 h to obtain ferric molybdate (FeMoO4) microsphere powder, wherein the average particle size of the ferric molybdate microspheres was 0.45 μm.
[0092] 200 mg of ferric molybdate microspheres were ultrasonically dispersed in 100 mL of deionized water for 10 min to prepare a suspension. 726 mg of Na₄Fe(CN)₆·10H₂O powder was added to the suspension, and the mixture was stirred continuously at room temperature for 5 h to carry out an ion exchange reaction, yielding a reaction solution. The reaction solution was centrifuged, washed, and then dried in a vacuum drying oven at 60 °C for 24 h to obtain the chemical formula […]. Iron-based Prussian blue cathode material.
[0093] from Figure 5-6 As can be seen from the above, the iron molybdate microsphere template has been successfully synthesized in Example 1 of this invention; from Figure 1-4 As can be seen from the data, the iron-based Prussian blue cathode material prepared in Example 1 of this invention has high crystallinity and a typical Prussian blue structure (No. 52-1907, face-centered cubic structure, space group Fm3m), indicating that Example 1 has successfully synthesized the chemical formula […]. The iron-based Prussian blue cathode material in Example 1 is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The average particle size of this hollow porous spherical structure is approximately 0.5 μm, the wall thickness is 0.098 μm, and the specific surface area is 92.5 m². 2 / g.
[0094] from Figure 12 as well as Figure 13 As can be seen from the results, the iron-based Prussian blue cathode material of Example 1 has excellent rate performance and cycle performance.
[0095] Example 2
[0096] Prepare an iron solution by mixing 0.808 g of Fe(NO3)3·9H2O and 8 mL of deionized water and stirring for 10 min; prepare an iron solution by mixing 0.354 g of ammonium heptamolybdate (NH4)6Mo7O. 24A molybdenum solution was prepared by mixing 4H2O and 8 mL of deionized water and stirring for 10 min. The molybdenum solution was then added dropwise to the iron solution. 20 mL of glycerol was added and the mixture was stirred for 1 h to prepare a mixed solution. The mixed solution was then transferred to a 90 mL Teflon-lined stainless steel high-pressure reactor and subjected to a solvothermal reaction at 190°C for 10 h to obtain the reaction product. The reaction product was centrifuged, washed three times with deionized water, and dried in a vacuum drying oven at 100°C for 12 h to obtain ferric molybdate (FeMoO4) microsphere powder with an average particle size of 5.5 μm.
[0097] 100 mg of ferric molybdate microspheres were ultrasonically dispersed in 20 mL of ethanol for 10 min, followed by the addition of 1 g of polyvinylpyrrolidone (average molecular weight 58,000) to prepare a suspension. 364 mg of Na₄Fe(CN)₆·10H₂O and 225 mg of trisodium citrate were dispersed in 40 mL of deionized water and stirred for min to prepare an aqueous solution of Na₄Fe(CN)₆·10H₂O. The prepared Na₄Fe(CN)₆·10H₂O aqueous solution was added to the suspension, and the mixture was stirred continuously at room temperature for 1.5 h for ion exchange reaction to obtain the reaction solution. The reaction solution was centrifuged, washed, and then dried in a vacuum drying oven at 120 °C for 8 h to obtain the product with the chemical formula […]. Iron-based Prussian blue cathode materials, such as Figure 7 As shown, the iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The average particle size of the hollow porous spherical structure is 6.5 μm, the wall thickness is 1.5 μm, and the specific surface area is 132 m². 2 / g.
[0098] Example 3
[0099] 0.477 g of FeCl2·4H2O and 30 mL of deionized water were mixed and stirred for 20 min to prepare an iron solution. 0.581 g of sodium molybdate Na2MoO4·2H2O and 30 mL of deionized water were mixed and stirred for 20 min to prepare a molybdenum solution. The molybdenum solution was then added dropwise to the iron solution and stirred for 1 h to prepare a mixed solution. The mixed solution was then transferred to a 90 mL Teflon-lined stainless steel high-pressure reactor and subjected to a solvothermal reaction at 125°C for 21 h to obtain the reaction product. The reaction product was centrifuged, washed three times with deionized water, and dried in a vacuum drying oven at 120°C for 8 h to obtain ferric molybdate (FeMoO4) microsphere powder, wherein the average particle size of the ferric molybdate microspheres was 3.9 μm.
[0100] 100 mg of ferric molybdate microspheres were ultrasonically dispersed in 50 mL of deionized water for 10 min to prepare a suspension. 363 mg of Na₄Fe(CN)₆·10H₂O powder was added to the suspension, and the mixture was stirred continuously at room temperature for 2 h to carry out an ion exchange reaction, yielding a reaction solution. The reaction solution was centrifuged, washed, and then dried in a vacuum drying oven at 120 °C for 8 h to obtain the chemical formula […]. Iron-based Prussian blue cathode materials, such as Figure 8 As shown, the iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The average particle size of the hollow porous spherical structure is 4.8 μm, the wall thickness is 1.2 μm, and the specific surface area is 82 m². 2 / g.
[0101] Example 4
[0102] Example 4 differs from Example 1 only in that 200 mg of ferric molybdate microspheres were ultrasonically dispersed in 100 mL of deionized water for 10 min to prepare a suspension; 726 mg of Na₄Fe(CN)₆·10H₂O powder was added to the suspension, and then the mixture was stirred continuously at room temperature for 5 h to carry out an ion exchange reaction, resulting in a reaction solution; after centrifugation and washing, the reaction solution was dried in a vacuum drying oven at 60 °C for 24 h to obtain the chemical formula […]. Iron-based Prussian blue cathode materials, such as Figure 9 As shown, the iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The average particle size of the hollow porous spherical structure is 0.8 μm, the wall thickness is 0.11 μm, and the specific surface area is 10⁸ m². 2 / g.
[0103] Example 5
[0104] Example 5 differs from Example 1 only in that 200 mg of ferric molybdate microspheres were ultrasonically dispersed in 100 mL of deionized water for 10 min to prepare a suspension; 1000 mg of Na₄Fe(CN)₆·10H₂O powder was added to the obtained suspension, and then the mixture was stirred continuously at room temperature for 5 h to carry out an ion exchange reaction, resulting in a reaction solution; all other conditions were the same, yielding a solution with the chemical formula […]. The iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The average particle size of the hollow porous spherical structure is 0.6 μm, the wall thickness is 0.085 μm, and the specific surface area is 68 m². 2 / g.
[0105] Example 6
[0106] Example 6 differs from Example 1 only in that 200 mg of ferric molybdate microspheres were ultrasonically dispersed in 100 mL of deionized water for 10 min to prepare a suspension; 600 mg of Na₄Fe(CN)₆·10H₂O powder was added to the obtained suspension, and then the mixture was stirred continuously at room temperature for 5 h to carry out an ion exchange reaction, resulting in a reaction solution; all other conditions were the same, yielding a solution with the chemical formula […]. The iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The average particle size of the hollow porous spherical structure is 0.58 μm, the wall thickness is 0.088 μm, and the specific surface area is 66 m². 2 / g.
[0107] Example 7
[0108] Example 7 differs from Example 1 only in that, in the step of preparing ferric molybdate (FeMoO4) microsphere powder, the mass of Fe(NO3)3·9H2O is 2.2g, and the mass of ammonium heptamolybdate (NH4)6Mo7O is... 24 The mass of 4H₂O was 0.83 g; all other conditions were the same, and ferric molybdate microspheres and a product with the chemical formula […]. The iron-based Prussian blue cathode material comprises iron molybdate microspheres with an average particle size of 0.428 μm. The iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The hollow porous spherical structure has an average particle size of 0.478 μm, a wall thickness of 0.081 μm, and a specific surface area of 63 m². 2 / g.
[0109] Example 8
[0110] Example 8 differs from Example 1 only in that, in the step of preparing ferric molybdate (FeMoO4) microsphere powder, the mass of Fe(NO3)3·9H2O is 2.0 g, and the mass of ammonium heptamolybdate (NH4)6Mo7O is... 24 The mass of 4H₂O was 2.75 g; all other conditions were the same, and ferric molybdate microspheres and a product with the chemical formula […]. The iron-based Prussian blue cathode material comprises iron molybdate microspheres with an average particle size of 0.408 μm. The iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The hollow porous spherical structure has an average particle size of 0.457 μm, a wall thickness of 0.08 μm, and a specific surface area of 55 m². 2 / g.
[0111] Comparative Example 1
[0112] 2.78 g of FeSO4·7H2O was dissolved in 100 mL of deionized water and stirred for 10 min to obtain an iron solution. 4.84 g of Na4Fe(CN)6·10H2O was dissolved in 100 mL of deionized water and stirred for 10 min to obtain an aqueous solution of Na4Fe(CN)6·10H2O. The iron solution was then added dropwise to the Na4Fe(CN)6·10H2O aqueous solution using a burette, and the mixture was stirred at room temperature for 8 h to obtain a reaction solution. This reaction solution was centrifuged, washed, and then dried in a vacuum drying oven at 60 °C for 24 h to obtain the chemical formula […]. Prussian blue cathode material.
[0113] from Figure 10-11 As can be seen from the data, the morphology of this iron-based Prussian blue cathode material is cubic nanoparticles with a specific surface area of 58.1 m². 2 / g.
[0114] from Figure 12 as well as Figure 14 As can be seen from the data, the iron-based Prussian blue cathode material in Comparative Example 1 has poor rate performance and cycle performance.
[0115] Comparative Example 2
[0116] Comparative Example 2 differs from Example 1 only in that the reaction solution was obtained after ion exchange reaction at room temperature for 5 hours; all other conditions were the same, yielding a solution with the chemical formula […]. The iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The average particle size of the hollow porous spherical structure is 0.488 μm, the wall thickness is 0.062 μm, and the specific surface area is 53 m². 2 / g.
[0117] Comparative Example 3
[0118] Comparative Example 3 differs from Example 1 only in that 2.1548 g of Fe(NO3)3·9H2O, 4 mL of HNO3, and 10 mL of deionized water were mixed and stirred for 30 min to prepare an iron solution; 1.412 g of ammonium heptamolybdate (NH4)6Mo7O was added. 24A molybdenum solution was prepared by mixing 4H₂O and 10 mL of deionized water and stirring for 30 min. This molybdenum solution was then added dropwise to the iron solution obtained earlier. Following this, 40 mL of glycerol was added and stirring was continued for 2 h to prepare a mixed solution. This mixed solution was then transferred to a 90 mL Teflon-lined stainless steel high-pressure reactor and subjected to a solvothermal reaction at 190 °C for 12 h to obtain the reaction product. The reaction product was centrifuged, washed three times with deionized water, and then dried in a vacuum drying oven at 60 °C for 24 h to obtain ferric molybdate (FeMoO₄) microsphere powder with an average particle size of 8.23 μm. Under the same conditions, the chemical formula […] was obtained. The iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The average particle size of the hollow porous spherical structure is 8.54 μm, the wall thickness is 2 μm, and the specific surface area is 43 m². 2 / g.
[0119] Comparative Example 4
[0120] Comparative Example 4 differs from Example 1 only in that, in the step of preparing ferric molybdate microspheres, a solvothermal reaction was carried out at 160°C for 5 hours to obtain the reaction product; all other conditions were the same, yielding the product with the chemical formula […]. The iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The average particle size of the hollow porous spherical structure is 0.262 μm, the wall thickness is 0.055 μm, and the specific surface area is 58 m². 2 / g.
[0121] Comparative Example 5
[0122] Comparative Example 5 differs from Example 1 only in that, in the step of preparing ferric molybdate microspheres, a solvothermal reaction was carried out at 160°C for 8 hours to obtain the reaction product; all other conditions were the same, yielding the product with the chemical formula […]. The iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The average particle size of the hollow porous spherical structure is 0.283 μm, the wall thickness is 0.068 μm, and the specific surface area is 66 m². 2 / g.
[0123] Comparative Example 6
[0124] Comparative Example 6 differs from Example 1 only in that 2.1548 g of Fe(NO3)3·9H2O, 4 mL of HNO3, and 10 mL of deionized water were mixed and stirred for 30 min to prepare an iron solution; 1.412 g of ammonium heptamolybdate (NH4)6Mo7O was added. 24A molybdenum solution was prepared by mixing 4H₂O and 10 mL of deionized water and stirring for 30 min. This molybdenum solution was then added dropwise to the iron solution obtained earlier. Following this, 45 mL of glycerol was added and stirring was continued for 2 h to prepare a mixed solution. This mixed solution was then transferred to a 90 mL Teflon-lined stainless steel high-pressure reactor and subjected to a solvothermal reaction at 190 °C for 12 h to obtain the reaction product. The product was centrifuged, washed three times with deionized water, and then dried in a vacuum drying oven at 60 °C for 24 h to obtain ferric molybdate (FeMoO₄) microsphere powder with an average particle size of 8.32 μm. Under the same conditions, the following product was obtained: The iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles. The average particle size of the hollow porous spherical structure is 8.65 μm, the wall thickness is 2.335 μm, and the specific surface area is 40 m². 2 / g.
[0125] Positive electrode sheets were prepared and assembled into CR2032 type batteries using the iron-based Prussian blue positive electrode materials obtained in Examples 1-8 and Comparative Examples 1-6, respectively.
[0126] The assembly method for the CR2032 battery is as follows: In an argon-protected glove box environment, the positive electrode material, Ketjen Black, and polytetrafluoroethylene are mixed evenly at a mass ratio of 70:20:10 to obtain a slurry. The slurry is then uniformly coated onto the surface of copper foil and dried in a vacuum drying oven at 100°C for 10 hours. Simultaneously, using metallic sodium and glass microfiber film (GF / D grade) as the counter electrode and separator, respectively, and a 1M NaClO4 solution dissolved in ethylene carbonate / diethyl carbonate (volume ratio 1:1) (containing 5% fluoroethylene carbonate (FEC)) as the electrolyte, the CR2032 battery is assembled.
[0127] Subsequently, constant current charge-discharge tests were conducted on each CR2032 battery at 25°C using the Xinwei Battery Testing System, with a voltage window of 2.0V-4.2V (vsNa / Na). + Between 1C and 2C, the electrical performance of each CR2032 battery was tested at different rates. The test results are shown in Table 1 below. In this table, 1C is 1C=140mA / g.
[0128] Table 1
[0129]
[0130] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0131] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. An iron-based Prussian blue cathode material, characterized in that, The molecular formula of the iron-based Prussian blue cathode material is: Wherein, 0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 1, and the iron-based Prussian blue cathode material is a hollow porous spherical structure formed by the stacking of cubic nanoparticles, the average particle size of the hollow porous spherical structure is 0.3 μm-8 μm, and the wall thickness of the hollow porous spherical structure is 0.08 μm-2 μm.
2. The iron-based Prussian blue cathode material according to claim 1, characterized in that, The specific surface area of the hollow porous spherical structure is 70 m². 2 / g-150m 2 / g.
3. A method for preparing the iron-based Prussian blue cathode material as described in claim 1 or claim 2, characterized in that, Includes the following steps: Ferric molybdate microsphere powder and solvent were formulated into a suspension; by Based on the condition that 0 < x ≤ 2, 0 < y ≤ 1, and 0 < z ≤ 1, Na4Fe(CN)6·10H2O powder or Na4Fe(CN)6·10H2O aqueous solution is placed in the suspension, and then stirred at room temperature and subjected to an ion exchange reaction. After separation and drying, iron-based Prussian blue cathode material is obtained. When Na4Fe(CN)6·10H2O powder is placed in the suspension, the solvent in the suspension includes at least water.
4. The method for preparing the iron-based Prussian blue cathode material according to claim 3, characterized in that, In the step of preparing a suspension from ferric molybdate microsphere powder and solvent, at least one of the following conditions must also be met: (1) The average particle size of the iron molybdate microspheres is 0.28 μm-6 μm; (2) The preparation method of the iron molybdate microsphere powder includes the following steps: preparing an iron source, a molybdenum source and a solvent into a mixed solution, then subjecting the mixed solution to a solvothermal reaction, and obtaining iron molybdate microsphere powder by separation and drying; (3) The solvent is selected from water and / or organic solvents.
5. The method for preparing the iron-based Prussian blue cathode material according to claim 4, characterized in that, The method for preparing the ferric molybdate microsphere powder also satisfies at least one of the following conditions: (1) The mass ratio of the iron source to the molybdenum source is 0.8:1-2.5:1; (2) The iron source is selected from at least one of ferric nitrate, ferric chloride, and ferric sulfate; (3) The molybdenum source is selected from ammonium heptamolybdate and / or sodium molybdate; (4) The temperature of the solvothermal reaction is 120℃-200℃, and the reaction time is 10h-24h; (5) The drying temperature is 60℃-100℃ and the drying time is 8h-24h.
6. The method for preparing the iron-based Prussian blue cathode material according to claim 3, characterized in that, In the step of placing Na4Fe(CN)6·10H2O powder or Na4Fe(CN)6·10H2O aqueous solution in the suspension, the mass ratio of the iron molybdate microsphere powder to Na4Fe(CN)6·10H2O is 1:3.5-1:4.
5.
7. The method for preparing the iron-based Prussian blue cathode material according to claim 3, characterized in that, When a Na4Fe(CN)6·10H2O solution is placed in the suspension, and the solvent in the suspension includes at least an organic solvent, at least one of the following conditions must also be met: (1) The suspension contains a surfactant, wherein the mass ratio of the iron molybdate microsphere powder to the surfactant is 1:10-1:30; (2) The aqueous solution of Na4Fe(CN)6·10H2O contains a complexing agent, wherein the mass ratio of Na4Fe(CN)6·10H2O to the complexing agent is 1.2:1-1.8:
1.
8. The method for preparing the iron-based Prussian blue cathode material according to any one of claims 3-7, characterized in that, The preparation method of the iron-based Prussian blue cathode material also satisfies at least one of the following conditions: (1) In the step of stirring and carrying out the ion exchange reaction at room temperature, the ion exchange reaction time is 1.5h-8h; (2) In the drying step, the drying temperature is 60℃-120℃ and the drying time is 8h-24h.
9. A cathode sheet prepared using the iron-based Prussian blue cathode material as described in claim 1 or claim 2.
10. A sodium-ion battery prepared using the positive electrode sheet as described in claim 9.
Citation Information
Cited By
Multi-metal ion doped Prussian blue sodium salt material as well as preparation method and application thereof
CN122117898A